LINEAR PROGRAMMING APPLIED TO A CONVEX PROGRAMMING TYPE - Montoro Alegre, Edinson Raúl (2012)
In the present’s paper studying a strategy for a typo of convex problem, we treat a linear programming problem whose coefficient of decision variables in the objective function has a nonlinear behavior. When the coefficients are constant the Simplex Method solves these problems without much difficulty, but when the coefficients are no longer constant and the Simplex does not work. We propose a technique that exploits the convex behavior of these coefficients and uses the theory of approximation by piecewise linear functions.